1985
DOI: 10.1111/j.1600-0447.1985.tb02537.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of 151 cases of anorexia nervosa

Abstract: One hundred and fifty-one patients (140 females - 11 males) with anorexia nervosa (AN) from three departments (child psychiatry, psychiatry, and internal medicine) were re-examined 4-22 years (average 12.5 years) after their first contact with the Rigshospital in Copenhagen. During the years 1960-76 the number of referrals was on the increase, and relatively more patients were treated in the psychiatric departments at the end than at the beginning of the period. Mean age was 16.6 years at onset, 19.0 years at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…However, this distribution en ables us to postulate the existence of two distinct periods in which susceptibility to AN is increased. The duration of the dis ease (1.46 years) is shorter than in other works [13,19,27] resembling the results of Theander [35] and Tolstrup et al [36], We think that this is an advantage when evalu ating the outcome of AN since it avoids the risk of selective bias towards patients with a tendency to chronicity. In fact, the rela tively low percentage of bulimia and vomit ing in our study (24 and 25%, respectively), less for example than that reported by Hsu et al [19], could be explained by the brief course of the illness.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, this distribution en ables us to postulate the existence of two distinct periods in which susceptibility to AN is increased. The duration of the dis ease (1.46 years) is shorter than in other works [13,19,27] resembling the results of Theander [35] and Tolstrup et al [36], We think that this is an advantage when evalu ating the outcome of AN since it avoids the risk of selective bias towards patients with a tendency to chronicity. In fact, the rela tively low percentage of bulimia and vomit ing in our study (24 and 25%, respectively), less for example than that reported by Hsu et al [19], could be explained by the brief course of the illness.…”
Section: Discussionmentioning
confidence: 53%
“…In fact, the rela tively low percentage of bulimia and vomit ing in our study (24 and 25%, respectively), less for example than that reported by Hsu et al [19], could be explained by the brief course of the illness. It could, however, also be explained by the particular sociocultural characteristics of our population which, un like others [3,5,19,36], includes a high proportion of working class patients. While this may be partially explained by the fact that the admitting hospitals were public in stitutions, it may also reflect the spread of AN among the working classes in the early 70s (the absolute values are determined by the composition of the different classes).…”
Section: Discussionmentioning
confidence: 87%
“…When there has been a history of anorexia nervosa, weight gain and body shape changes accompanying pregnancy can provoke extreme distress (Crisp, 1984). Pregnancy after anorexia nervosa is infrequently reported, occurring in less than 10% of patients (Hsu, 1980;Hsu, Crisp, & Harding, 1979;Tolstrup, Brinch, Isager, Nielsen, Nystrup, Severin, & Olesen, 1985) and may require induction of ovulation (Hart, Kase, & Kimball, 1970). We describe two cases, different from the four pregnancies with spontaneous ovulation previously described (Abraham, Beumont, Booth, & Smith, 1981;Ho, 1985;Strimling, 1984;Weinfeld, Dubay, Burchell, Millerick, & Kennedy, 1977): both gained weight during pregnancy and had normal-weight babies.…”
Section: Introductionmentioning
confidence: 99%
“…A similar relationship has been demonstrated in other serious medical illnesses . Patients with anorexia nervosa have been shown to deplete protein in the course of becoming ill (Russell et al, 1983), and their course may become chronic as has been demonstrated in 20% or more of sufferers (Tolstrup et al, 1985;Ratnisurya, Ester, Szmukler, & Russell, 1991). The mortality rate in these patients is not inconsiderable, approaching the chronicity rates in long-term outcome studies.…”
mentioning
confidence: 99%